Assessing the Role of Flow Cytometry Immunophenotyping in Acute Leukemia and Aberrant Expression Detection in the Indian Population - Singh, Namrata; Gohil, Sanjay; Mathias, Jyothi; Haryan, Reshma; Dhole, Shamika; Ramchandran, Shibani; Jatale, Raj; Chadha, Kirti (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Background: Acute Leukemia (AL) is one of the malignant hematological disorders, which is caused by the uncontrolled proliferation of abnormal hematopoietic cells. On the basis of different methods of diagnosis, Acute Leukemia has been divided into different types based on morphology, antigen presentation, and genetic abnormalities. Aim: To study the distribution of Acute Leukemia cases, and the expression of commonly used Cluster of Differentiation (CD markers) in sub-classification of Acute Leukemia and aberrant expression of these markers. Methods: The retrospective study was conducted at a Global Reference Lab in Mumbai from January 2017 to December 2021 on 1538 Acute Leukemia cases diagnosed based on 20% & more blasts on morphology and Flowcytometry immunophenotyping. The data were analyzed by using “R Studio version 1.4.1103”. Descriptive analyses were made to obtain the frequency and percentage of Acute Leukemia classification in the population, in addition to the characteristics of the sample, Age, and Gender. Results: Out of 1538 Acute Leukemia (AL) cases, Acute Myeloid Leukemia (AML) was found to be more common (59.49%) than Acute Lymphoid Leukemia (ALL) (39.27%). Age distribution showed that ALL was more common in the Pediatric age group, whereas AML was seen more commonly in adults and older age. In further analysis of ALL, B-ALL was found to be higher as compared to T-ALL. CD33 (92.74%), CD19 (100%), and CD7 (97.79%) were the most sensitive markers for AML, B-cell, and T-cell, respectively. CD7, CD33, and CD13 were the most commonly expressed aberrant markers found in them, respectively. The immunophenotyping of acute leukemia not only differentiates leukemia into two different types, AML or ALL, but further subcategories as well. Aberrant expression of myeloid markers in ALL has been described to have a poor prognosis compared to one that does not show aberrations. Conclusion: Flowcytometry immunophenotyping is indispensable fastest and most precise tool in defining the lineage of Acute Leukemia and identification of Mixed Phenotypic Acute Leukemia (MPAL) and Undifferentiated Leukemia. Aberrant expression of markers guides further cytogenetic and molecular studies to a great extent and identification of blasts during assessment of minimal residual disease. The evaluation of aberrant expression with genetic phenotype and prognostic and therapeutic implications.